Diagnosis of Human Leptospirosis by Monoclonal Antibody-Based Antigen Detection in Urine - Saengjaruk, Patcharin (American Society for Microbiology, 2002)
Hybridomas secreting specific monoclonal antibodies (MAb) to all members of the genus Leptospira (clone LF9) and those that are specific only to the pathogenic species (clones LD5 and LE1) were produced. MAb LF9, which was immunoglobulin G1 (IgG1), reacted to a 38-kDa component of the sodium dodecyl sulfate-polyacrylamide gel electrophoresis-separated whole-cell lysates of all Leptospira spp., while MAb LD5 and MAb LE1, which were IgG1 and IgG2a, respectively, reacted to the 35- to 36-kDa components of all serogroups of the pathogenic species of Leptospira. The MAb LD5 was used in a dot blot-enzyme-linked immunosorbent assay (dot-ELISA) for detecting Leptospira antigen in urine samples serially collected from two groups of patients diagnosed with leptospirosis, i.e., 36 clinically diagnosed patients and 25 Leptospira culture confirmed patients. Their serum samples were tested serologically by IgM Dipstick assay, indirect immunofluorescence assay (IFA), and/or microscopic agglutination test (MAT). Urine samples of 26 patients diagnosed with other illnesses and 120 healthy individuals served as controls. For the first group of patients, who had been ill for an average of 3.4 days before hospitalization, the IgM Dipstick test, IFA, and MAT were positive for 69.4, 70.0, and 85.7% of patients, while the Leptospira antigenuria tested by the MAb-based dot-ELISA was positive for 75.0, 88.9, 97.2, 97.2, and 100% of patients on days 1, 2, 3, 7, and 14 of hospitalization, respectively. All but 1 of 11 patients whose serum samples collected on the first day of hospitalization were IgM seronegative, were positive by urine antigen test on day 1. This is strong evidence that detection of antigen in urine can provide diagnostic information that could be useful in directing early therapeutic intervention. The MAT was positive in 10 of 12 patients (83.3%) of the 25 culture-positive Leptospira patients who had been ill for an average of 5.04 days before hospitalization, and the Leptospira antigen was found in 64.0, 84.0, 96.0, 100, 100, 100, and 100% of the patients' urine samples collected on days 1, 2, 3, 4, 5, 6, and 7 of hospitalization, respectively. Leptospira antigenuria was found in 3 of the 26 patients diagnosed with other illnesses and 1 of the 120 healthy controls. The reasons for this positivity are discussed. The detection of antigen in urine by the monoclonal antibody-based dot-ELISA has high potential for rapid, sensitive, and specific diagnosis of leptospirosis at a low cost.